2004
DOI: 10.1023/b:caco.0000027481.48153.97
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Cancer Risk in Korean Men and Women

Abstract: In Korea, smoking is an independent risk factor for a number of major cancers. The findings affirm the need for aggressive tobacco control in Korea in order to minimize the epidemic of smoking-caused disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
159
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 16 publications
12
159
2
3
Order By: Relevance
“…Although we observed a clearer reduction in risk for papillary vs follicular cancers, this difference was not significant. However, there were only 64 follicular cancers in this study.Given the strong, positive correlation between alcohol and smoking, and the evidence linking smoking with a reduced risk of thyroid cancer (Mack et al, 2003;Jee et al, 2004;Nagano et al, 2007), residual confounding by smoking may have biased our results away from the null. However, this seems unlikely as a stronger inverse association for alcohol was observed for never when compared with ever cigarette smokers.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Although we observed a clearer reduction in risk for papillary vs follicular cancers, this difference was not significant. However, there were only 64 follicular cancers in this study.Given the strong, positive correlation between alcohol and smoking, and the evidence linking smoking with a reduced risk of thyroid cancer (Mack et al, 2003;Jee et al, 2004;Nagano et al, 2007), residual confounding by smoking may have biased our results away from the null. However, this seems unlikely as a stronger inverse association for alcohol was observed for never when compared with ever cigarette smokers.…”
mentioning
confidence: 87%
“…The rapid increase in thyroid cancer incidence in the United States over the past three decades may be related to changes in certain environmental exposures, as well as increased surveillance and more widespread use of sensitive diagnostic tools (Enewold et al, 2009). However, despite many retrospective studies, few risk factors have been established other than childhood exposure to ionizing radiation (Dal Maso et al, 2009).Certain studies have suggested an inverse association between alcohol and thyroid cancer risk, but this may be confounded by cigarette smoking, which is correlated with alcohol consumption and has been inversely related with thyroid cancer (Mack et al, 2003;Jee et al, 2004;Nagano et al, 2007). However, no association was observed in a pooled analysis of 14 case -control studies after adjusting for smoking (Mack et al, 2003), or in two prospective studies with fewer than 200 cases (Iribarren et al, 2001;Navarro Silvera et al, 2005), although these studies were consistent with a small reduction in risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Active smoking and longer smoking duration are associated with increased risk for bladder cancer, when compared with neveror former-smokers. [14][15][16] Smoking intensity (cigarettes smoked per day or pack-years smoked) is not a separate independent risk variable. 17 …”
Section: Epidemiology Of Bladder Cancermentioning
confidence: 99%
“…Of interest, growing evidence has demonstrated a remarkable difference in genetic and epigenetic factors leading to this neoplasm between East Asian and Western populations (Gazdar et al, 2004;Toyooka et al, 2003). In Korea, prevalence of male smoking is among the highest in the world, and mortality rates from smoking-related cancers, particularly lung cancer, are escalating (Jee et al, 2004). Therefore, advances in understanding of the molecular pathogenesis of lung cancer are critical to conquering lung cancer.…”
Section: Introductionmentioning
confidence: 99%